Regional differentiation of revenues collected by local governments of Lithuania - Ginevičius, Romualdas; Slavinskaitė, Neringa; Gedvilaitė, Dainora (Business, Management and Economics Engineering, 2014)
The article focuses on the issue of municipal funding from revenues collected by local governments and the state budget of Lithuania. In addition, it offers an evaluation of the Lithuanian practice in this field, discusses used methodological approaches and overviews practical experience of other countries as well as the relevant theory. Furthermore, it considers theoretical issues of local tax and tax distribution between levels of local government. Finally, it gives general principles of tax distribution and administration. The results of this investigation point to fundamental problems, relating the misbalance in funding of local governments with regional differentiation. The growth in disparities of municipal revenues demands a better redistribution of income, which includes an increasing amount of grants. However, the current system used for funding of local governments limits possible solutions that could address these problems. It should be considered that in 2009–2013, the lowest amount of municipal income per resident was identified in Vilnius County; whereas the highest amount was found in Utena (2009), Alytus (2010–2012) and Šiauliai (2013) counties.